大學生選課後悔與動機干擾研究：檢驗後悔因應策略的中介效果與社會支持的調節效果 Effect of Regret on Motivational Interference Among College Students: Regret Coping Strategy as a Mediator and Social Support as a Moderator - 陳慧娟 Huey-Jiuan Chen; 簡洧晴 Wei-Ching Chien (National Taiwan Normal University, 2020)
本研究旨在瞭解大學生選課後悔、因應策略、社會支持與已選擇課程動機干擾的關係，並探討後悔因應策略的中介效果，以及社會支持的調節效果。本研究的參與者為 516 位就讀臺灣各公私立大學的學生，其中男生 241 人，女生 275 人，經立意取樣方式邀請其填答問卷。 研究工具包括研究者自編之「後悔量表」、「動機干擾量表」、「後悔因應策略量表」與「社會支持量表」。所得資料以描述性統計、變異數分析、相關與迴歸分析進行統計考驗。主要研究結果如下：一、「後悔」與「動機干擾」有顯著正相關；二、「反芻思考」策略可正向中介後悔對動機干擾的影響；三、「聚焦現在」的認知重新評估策略無法中介後悔對動機干擾的影響；四、「聚焦未來」的認知重新評估策略可負向中介後悔對動機干擾的影響；五、社會支持對後悔與動機干擾間的關係沒有顯著調節效果，但較高水平的情感支持可緩解後悔與動機干擾的正向關聯強度。本研究針對以上結果進行討論與研擬具體建議，以提供教育實務與未來研究之參考。 The study explored the relationships among regret, regret coping strategy, perceived social support, and motivational interference during the elective courses; additionally, it examined the mediating and moderating effects of both regret coping strategy and social support on college students. The survey was conducted through purposeful sampling, and 516 college students studying in Taiwan's public and private universities (241 male and 275 female students) were invited to respond to the questionnaires. The research instruments comprised a self-designed regret scale, motivational interference scale, regret coping strategy scale, and social support scale. The data analysis was performed using descriptive statistics, t tests, and regression analysis. The main findings were as follows: (1) A significant positive correlation was noted between regret and motivational interference. (2) The regret coping strategy of rumination fully negatively mediated the relationship between regret and motivational interference. (3) The present-focused reappraisal strategy did not mediate the effect of regret on motivational interference. (4) The future-focused reappraisal strategy negatively mediated the effect of regret on motivational interference. (5) Perceived overall social support did not moderate the effect of regret on motivational interference; however, higher the level of emotional support, stronger the positive correlation between regret and motivational interference.According to the study findings, suggestions were provided to high school teachers, counselors, parents, and future researchers.